Desain Sistem Pembangkit Lisrik Tenaga Surya Pada Tambak Udang sebagai Penggerak Aerator - Idris, Ahmad Rosyid; Thaha, Sarma (Politeknik Negeri Ujung Pandang, 2019)
Indonesia is a tropical region with very large solarenergy where an average daily insulation of 4.5 - 4.8 KWh / mÂ² /day. Based on this fact, solar energy is a potential form ofrenewable energy to be developed. This study aims to design aPLTS system which is the initial stage of planning PLTS systemdevelopment. This system Design uses Matlab software byutilizing the Matrix Unit Interface (GUI) Matlab to calculatethe amount of electrical load to be used, battery capacityrequirements, number of solar modules and large capacity ofthe inverter to be used. Location of the measurement datacollection takes place in the city of Pinrang, area of the Suppasub-district shrimp farm. Measurements are conducted todetermine how much solar radiation and air temperature in thepond area.